Monitoring report on fertilizer validation trials under the Kenya fertilizer access and nutrient use efficiency program - Kinyua, Michael; Mathu, Samuel; Kihara, Job; Nkomo, Mandlenkosi (2024)
The Excellency in Agronomy (EiA) initiative in collaboration with Africa Fertilizer Agribusiness Partnerships (AFAP), Kenya Agriculture and Livestock Research Organization (KALRO), President’s Economic Transformation Secretariat (PETS), University of Eldoret and the Ministry of Agriculture are conducting fertilizer validation trials in Nandi County of Kenya. The aim of the fertilizer validation exercise is to: 1) Establish what are the localized NPK fertilizer recommendation for maize 2) Assess maize response to application of lime 3) Increase maize yields and profitability by at least 20%. To achieve the above objectives, three fertilizer recommendations were identified/developed for validation: 1) Agwise recommendation: different rates of NPK (17:17:17) depending on the sub-County’s soil nutrient levels 2) Agwise recommendation + lime: NPK (17:17:17) + Lime guided by sub-County’s soil pH levels 3) Blanket recommendation: Ministry of Agriculture recommendation for the County applied in form of Di- ammonium phosphate (DAP).